Pengkajian Problematika Istihadhoh dalam Perspektif Hadis - Jauharah Khairun Nisa (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about istihadhoh. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about istihadhoh in Muslim history No. 501. The results and discussion of this study indicate that the status of the hadith is hasan quality, which is the same as the sahih hadith, which can be used as hujjah. This study concludes that the hadith narrated by Muslim No. 501 is relevant to be used as a means of knowledge about menstruation and istihadhoh.